Technical Efficiency in Cashew Nut Production in Kilifi County, Kenya - R.K, Koech; S.M, Mwakubo; P.M, Nyangweso (IJRDO - Journal of Business Management, 2016)
The agricultural sector continues to be an important pillar of the coastal economy in Kenya. Cashew nuts together with coconuts are the principal cash crops grown in Kilifi County. Even though efforts have been made to improve productivity in the smallholder cashew sector, not much has been realized and productivity continues to stagnate. It seems that production technologies generated in research institutions have had minimal impact on efficiency and resource productivity. This study was therefore carried out with the main aim of analyzing the economic factors that influence production of cashewnut in Kilifi County. This was done by measuring the technical efficiency of cashew nut production and isolating the determinants of these efficiencies. The study used ordinary least squares (OLS) and maximum likelihood estimates (MLE) procedures to estimate parameters of identified input variables. The model also estimated technical efficiencies of individual farmers. Results showed that land area under cashew and extension service were significant determinants of output at five one per cent level of significance respectively while labour was significant at ten per cent